Hole-selective-molecule doping improves the layer thickness tolerance of PEDOT:PSS for efficient organic solar cells - Bin Zhao; Xiaozhen Huang; Sein Chung; Min Zhang; Yufei Zhong; Anhai Liang; Zhenmin Zhao; Chaofeng Zhu; Jingjing Zhao; Seunghyun Kim; Jimin Kim; Ming Wang; et al. (eScience)
When used in organic solar cells, poly (3,4-ethylenedioxythiophene)-poly (styrenesulfonate) (PEDOT:PSS) aligns interfacial energy levels, promotes hole extraction, blocks electrons, and optimizes the active layer’s morphology. However, with an optimal thickness of approximately 30–40 ​nm, PEDOT:PSS has insufficient layer thickness tolerance, owing to its low conductivity and hole extraction property. Herein, a hole-selective-molecule doping strategy is proposed to enhance the properties of PEDOT:PSS by introducing MPA2FPh-BT-BA (abbreviated as 2F) into its layer. 2F assembles at the anode to form interfacial dipoles due to its unique donor–acceptor–anchor molecular configuration, altering the anode work function and hole-selective extraction. Additionally, 2F improves the aggregation properties of PEDOT:PSS by forming hydrogen bonds with the PSS group, enhancing the conductivity characteristics. These changes in the PEDOT:PSS layer further influence the overlaying morphology, leading to increased crystalline features of PM6 and the bulk heterojunction of PM6:Y6. When a 2F-PEDOT:PSS (2FPP) layer is used, power conversion efficiencies of 18.3%, 19.2%, and 19.1% are achieved in PM6:Y6, PM6:BTP-eC9, and PM6:L8-BO devices, respectively, outperforming counterparts with PEDOT:PSS. Specifically, the performance of PM6:Y6 devices with a 2FPP layer of 170 ​nm remains at > 15%, providing valuable guidance for designing a thickness-insensitive hole transport layer for high-efficiency organic solar cells.